UNFAIR DISMISSAL FOR AUSTRALIAN WORKERS: THE HUNDRED-YEAR JOURNEY - Kim Southey (Asian Academy of Management Journal, 2015)
This paper examines the journey Australia traversed in the development at of the unfair dismissal protections it provides the majority of its workers, since the nation's Federation in 1901. Historically, the country's Constitutional "heads of power" were intended to prohibit the federal government from regulating individual aspects of the employment relationship. Over time, such interpretations of the constitutional powers were challenged by governing parties, resulting in the modern-day, "national" unfair dismissal protections afforded to the majority of workers. The journey Australians traversed during the architecture of their current unfair dismissal legislation provides a lesson on a government's ability to conjure significant influence on individual arrangements between management and workers. Despite Australia's participation in the worldwide, neoliberal push to deregulate labour markets, the protection of workers from unfair dismissal is an explicit matter in the employment relationship attracting increased regulation through industrial legislation. This paper culminates in reporting the consequences facing employers who improperly administer dismissals and how employers can take steps to mitigate such risks.